Development of an Indonesian Language Learning Video for Grade VIII of Junior High School Negeri 2 Gunungsitoli Utara - Hilda Natalia Hulu; Riana; Kesaktian Telaumbanua (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Finding a workable, practical, and successful way to create instructional films for the Indonesian language at SMP Negeri 2 Gunungsitoli Utara based on persuasive text writing content is the goal of this research. Research and development encompasses this sort of study. The five-stage ADDIE paradigm is used for development; they are as follows: analysis, design, development, implementation (or execution), and evaluation. The Indonesian language learning film went through a rigorous testing process that included three separate groups of specialists (materialists, linguists, and design experts) and was piloted in eighth grade at SMP Negeri 2 Gunungsitoli Utara. Researchers found that material expert validators gave the video a 92% validity rating at revision II, language expert validators gave it a 100% validity rating, and design expert validators gave it a 95% feasibility rating, all in relation to the persuasive text writing material taught at SMP Negeri 2 Gunugsitoli Utara. The field test had a very practical category score of 96% and a small group test score of 93% for the learning video's practicality. With a classical completion percentage of 95%, the learning film has also been evaluated and shown to be quite successful. This study's findings suggest that the ADDIE-based instructional video for the Indonesian language at SMP Negeri 2 Gunugsitoli Utara has fulfilled all criteria and is ready for usage.